Reliable data transmission: An IoT health-based paradiam - Dalal Abdulmohsin Hammood; Mahmoud Shuker Mahmoud; Ahmed Alkhayyat; Hasliza A. Rahim; R. Badlishah Ahmad (Institute of Advanced Engineering and Science, 2020)
A WBAN can be spread over a person's body, so; posing, dressing, moving of muscles, degree of heat of bodies as well as weather changes in general affect connections among sensors as well as desired point. Secondly, information collected via every sensor can be connected to a person's course of life; so, it can be considered as significant to guarantee that the collected information ought to be given to desired point competently. In this work, a critical cooperating communicating protocol to WBAN established on information has been suggested, called critical data transmission using transmission mode selection (CD-TMS) method established for the architecture of star topology. In the beginning, we performed a studying, also we established a system model can be looked at according to channel los of path, effective transmitting possibility, as well as the out of work time possibility. Thirdly, relaying selecting can be used accompanied by CD-TMS, that lets just the most successful relaying take part in cooperating in a spread manner. Simulating as well as numeral outcomes illustrate that CD-TMS has the ability to develop the performing of a network under common terms comparing with direct transmission mode (DTM) IEEE 802.15.6 CSMA as well as benchmark.